Auditory and visual attention assessed with PET - O'Leary, D.S.; Andreasen, N.C.; Hurtig, R.R.; Torres, I.J.; Flashman, L.A.; Kesler, M.L.; Arndt, S.V.; Cizadlo, T.J.; Ponto, L.L.B.; Watkins, G.L.; Hichwa, R.D. (Human brain mapping, 1997)
Brain mechanisms involved in the maintenance of attention to auditory and visual stimuli at different spatial locations were assessed using positron emission tomography with [15O]water to measure regional cerebral blood flow (rCBF) changes in 13 normal volunteers. Simultaneous auditory [dichotically presented consonant‐vowel‐consonants (CVCs)] and visual stimuli (vertically oriented, CVCs presented to the left and right of fixation) were presented on every trial. In different conditions subjects attended for targets in a specified stimulus channel (left or right ears or left or right visual fields) while maintaining fixation on a central x. Attending left or right for auditory stimuli increased rCBF in primary auditory cortex in Heschl's gyrus and in temporal lobe auditory association cortices in both hemispheres. Attending left or right for visual stimuli did not change rCBF in primary visual cortex, and only attention to the right significantly increased rCBF in contralateral occipital cortex. Visual attention caused significant rCBF changes in a widespread network that included frontal, parietal, and temporal cortical regions as well as the cerebellum, whereas rCBF changes due to auditory attention were largely localized in the temporal lobes. The results suggest that spatially directed attention is mediated by different mechanisms in the auditory and visual modalities. Hum. Brain Mapping 5:422–436, 1997. © 1997 Wiley‐Liss, Inc.